Ultrastructural alterations in Phacus brachykentron (Euglenophyta) due to excess of organic matter in the culture medium - Nannavecchia, Paula Silvia (2014)
Morphological and ultrastructural changes induced by exposure to excess of organic matter were analyzed in Phacus brachykentron (Pochm.). The cells were isolated from sites in Matanza River, Buenos Aires, Argentina, which have a high degree of organic matter contamination coming from waste waters discharges of the meat industry. Master strains were cultured on soil water medium and a toxicity bioassay was performed. As a result of the enriched medium, several morphological and ultrastructural cellular alterations were observed by optical, scanning, and transmission electron microscopy. Among these, we can point out changes in cell dimensions, remarkable widening of some pellicle bands, increased number and volume of paramylon grains, displacement of the nucleus from the central to the lateral position, some chloroplasts with their thylakoids disordered, and cell lysis. The response to organic enrichment was very fast, i.e. during the 48 h of the bioassay. Therefore, any significant increase of organic matter would rapidly affect wild euglenoids. Our results suggest that the alterations observed, such as the presence of large intracellular paramylon bodies or the deformation of euglenoid cells in natural samples, have the potential to be used as environmental bioindicators.